THE PHENOMENON OF SIRI MARRIAGE AND ITS IMPLICATIONS FOR ISLAMIC FAMILY LAW - Sawaluddin Siregar; Indra Sakti; Iqbal Pinayungan Munthe; Putra Halomoan Hasibuan; Purnama Hidayah Harahap (PT. Jurnal Center Indonesia Publisher, 2026)
From an Islamic perspective, marriage is not merely a civil matter, nor merely a family or cultural matter, but also relates to religious issues and events, as it is conducted to fulfill the provisions of Allah SWT and the Prophet Muhammad (peace be upon him). A siri marriage is a marriage conducted without official state registration, thus having significant legal implications for women and children. While religiously, this marriage is considered valid, from a state legal perspective, unregistered marriages result in women losing their rights as wives, such as the right to maintenance, inheritance rights, and legal protection within the household. Furthermore, women in siri marriages lack a strong legal basis to file for divorce or assert their rights in court. Meanwhile, children born from siri marriages have only a civil relationship with their mothers, thus facing obstacles in obtaining birth certificates listing the father's name, inheritance rights, and rights to care and education from the father. Siri marriages are also often used as a way to freely practice polygamy without following proper procedures.